The Effect of Sol-Gel Temperature and Solvent Polyethylene Glycol (PEG) in ZnO-TiO2 Photocatalyst Activity as Degrader of Textile Dyeing Liquid Waste - Tanti Haryati; Novita Andarini; Siti Mardhiyah (ALCHEMY Jurnal Penelitian Kimia, 2016)
The use of TiO2  powder  as photocatalyst still provides some disadvantages such as the difficulties in regenerate ion, the low adsorption and turbulence . These problems can be overcomed by providing the photocatalyst as a composite of ZnO-TiO2. This research aims to  investigate  the  effect  of  composition  of  solvent  and  temperatureof  synthesis  on  the quality  and  photocatalytic  activity  of  ZnO-TiO2  which  was  prepared  by  sol-gel  method. The  photocatalytic  activity  was  determined  by  applying  the  composite  in  degradation  of Procion  Red  MX-8B  under  irradition  of  UV  light  for  24  hours.  The  procion  red concentration after degradation was determined by UV-Vis spectrophotometer. Meanwhile the effect of synt hesis temperature on crystal structure  of composite  was studied by XRD. The results show that the composite which was prepared by PEG 1500 at 1:4 of moles ratio and at 70  °C of  synthesis temperature has  highest degradation  percentage,  i.e. 55.375 % and photocataltic activity of 3.561 x 10-7mg/cm2s.